Esther Cohen, La palabra inconclusa. (Ensayos sobre Cábala) - Ernesto de la Peña (Medievalia)
Esther Cohen, La palabra inconclusa. (Ensayos sobre Cábala), México: Taurus-Universidad Nacional Autónoma de México, 1994.